Psychological consequences of sport injury on mental well-being of elite athletes in Ibadan, Nigeria (2021)
Injuries are an unavoidable and inevitable part of sport participation. Some injures car be managed easily, while some disrupt and impose a threat on the mental health of the athletes. Some injuries heal on time, linger and some lead to transitioning from the sport. Either minor or major, an injury sustained does not only affect the physical well-being of the athletes but also their mental well-being. Little concern is given to the mental aspect of the outcomes of psychological consequences of sport injury. Therefore, the purpose of this study was to examine the psychological consequences of sport injury on the mental well-being of elite athletes in Ibadan, Nigeria. A descriptive survey research design was employed. The participants were a hundred (100) (Male=63, Female=37) elite athletes of Oyo State Sports Council purposively sampled from various sports. The instruments used for data collection were: The Perceived Stress Scale (PSS) Centre for Epidemiologie Studies-Depression Scale (CES-DS), Athletic Identity Measurement Scale (AIMS), Modified Revised UCLA Loneliness Scale (MRULS), Sport Injury Anxiety Scale (SIAS) and The Short-Form 8 (SF-8) Health Survey. The data collected were analysed using multiple regression to test the hypotheses. Results of the study showed that there was a significant joint contribution of psychological consequences of sport injury on mental well-being of elite athletes (F (5.94) = 110.272, R = 924, R2 =.854. Adjusted R2 =.851, p<0.05). Psychological consequences factors of sports injury of stress (β = -.667. t= -15.007), depression (β = -.250. t= -6.852), isolation (β = -.197, t= -6.065) and fear of re-injury (β = -.210, t= -4.152) were significance while loss of identity (β= -.050, t= -1.316, p>0.05) was not significant. It was therefore recommended that athletes, coaches, support staff among others should be educated on symptoms of mental health and coping resources to be employed and also, optimum mental health care supports should be rendered to the athletes